Advances in management of Guillain–Barré syndrome. Issue 5 (October 2018) - Doets, Alex Y.; Jacobs, Bart C.; van Doorn, Pieter A.
Abstract : Purpose of review: The clinical presentation of Guillain–Barré syndrome (GBS) is highly variable, which can make the diagnosis challenging. Intravenous immunoglobulin (IVIg) and plasma exchange are the cornerstones of treatment since decades. But despite these treatments, 25% initially progress in muscle weakness, 25% require artificial ventilation, 20% is still not able to walk independently after 6 months, and 2–5% die, emphasizing the need for better treatment. We summarize new developments regarding the diagnosis, prognosis, and management of GBS. Recent findings: GBS is a clinical diagnosis that can be supported by cerebrospinal fluid examination and nerve conduction studies. Nerve ultrasound and MRI are potentially useful techniques to diagnose inflammatory neuropathies. Several novel infections have recently been associated to GBS. Evidence from experimental studies and recent phase 2 clinical trials suggests that complement inhibition combined with IVIg might improve outcome in GBS, but further studies are warranted. Prognostic models could guide the selection of patients with a relatively poor prognosis that might benefit most from additional IVIg or otherwise intensified treatment. Summary: New diagnostic tools may help to have early and accurate diagnosis in difficult GBS cases. Increased knowledge on the pathophysiology of GBS forms the basis for development of new, targeted, and personalized treatments that hopefully improve outcome.